Should knowledge be shared generously? Tracing insights from past to present and describing a model. Issue 4 (11th July 2016) - Anand, Amitabh; Walsh, Isabelle
Abstract : Purpose: The purpose of this study is to attempt to answer the following questions: Are people generous at work places? How often do we see people willing to share, when someone seeks knowledge from them without any expectation? What's the point in having knowledge when somebody doesn't share it? Then again, why do firms, reward employees to share their knowledge? ¬ ¬? Does sharing knowledge between people need a commercial acceptance or rewarding inspiration? In firms, people, who do not have relevant work-related knowledge, seek it from others. Thus, this implies that people can either share their knowledge or hoard knowledge or share partial knowledge. This research shows that sharing knowledge has existed for centuries and has been practised through generosity, with proof that the more you share the more you obtain in return. The authors analyse the role of generosity in sharing knowledge by tracing insights from literature, religion, science and modern day management scholarly views, and they show how it can lead firms to succeed. In this paper, the authors will propose a direction for future researchers on how developing generosity helps towards sharing knowledge. They also propose a model of generosity based on literature and its interpretation. Design/methodology/approach: This paper is based on extensive reviews of literature, articles and opinions from scholars. The authors use a keyword protocol to investigate articles from Google scholar and other sources on generosity and knowledge sharing. Findings: This paper finds significant relationships and validated shreds of evidence on how generosity towards knowledge sharing has helped humanity in the past and how generosity can help firms to succeed. Originality/value: This paper is the first of its kind in trying to explore how developing generosity among people can play a role in facilitating knowledge sharing for firms to succeed. This further suggests a new direction of research for scholars engaged in exploring the role of generosity with a proposed model.